2016
DOI: 10.1017/s0022215116009798
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adult acquired subglottic stenosis

Abstract: Obesity and diabetes are significant risk factors for acquiring subglottic stenosis. Further investigations are required to determine if obesity is also a predictor for failed tracheostomy decannulation in subglottic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
1
34
1
1
Order By: Relevance
“…GERD has been suggested to contribute to the pathophysiology of SGS. Reports of its coexistence in patients with SGS range from 45% to 69%, 9,10,13 and our results (60.4%) are consistent with this. However, for the purpose of this study, the presence of GERD was assumed if patients were listed in the electronic medical record as taking an antireflux medication.…”
Section: Discussionsupporting
confidence: 92%
“…GERD has been suggested to contribute to the pathophysiology of SGS. Reports of its coexistence in patients with SGS range from 45% to 69%, 9,10,13 and our results (60.4%) are consistent with this. However, for the purpose of this study, the presence of GERD was assumed if patients were listed in the electronic medical record as taking an antireflux medication.…”
Section: Discussionsupporting
confidence: 92%
“…Age, obesity, longer duration of MV, previous history of MV, and more than once endotracheal tube change during the period of mechanical ventilation were found as possible risk factors for post-intubation stenosis. In previous studies, tracheal tube size, material of tube cuff [19], female gender [20], obesity [21], and smoking [22] were possible risk factors of post-intubation stenosis.…”
Section: Discussionmentioning
confidence: 95%
“…The ring cartilage reacts particularly sensitively to local trauma with the development of recurrent tracheal stenosis caused by excessive regeneration processes with osteoid expression of osteoblasts and mineralization in an acidic environment [25]. Beyond the tracheotomy technique, overweight, diabetes and reflux, accompanied by chronic inflammatory reactions, are risk factors for the development of subglottic stenosis [26]. A recent analysis of 262 cases suggested that COPD, nicotine abuse, OSAS, hypertension and microcirculation disorders are the comorbidities responsible for the development of laryngotracheal stenosis following tracheostomy [27].…”
Section: Discussionmentioning
confidence: 99%